Development of Microreplication Process - Micromolding - Yuan, Shu (Taylor and Francis Inc., 2003)
A microreplication process, micromolding, was developed to replicate three-dimensional microcomponents. It included modifying a conventional molding machine, developing a thermal control unit to control the mold temperature, and developing a vacuum unit to evacuate the microcavity before filling it with plastic melt. Focused ion beam sputtering, a maskless patterning of material, was used to fabricate a microcavity that was then used as a mold insert. Feasibility of the micromolding process was investigated by simulation, and results were verified with the replication of polymer microcomponents (e.g., microgear, gear-train). Commercial simulation software was used to reveal possible issues in micromolding by integrating the microcomponent with a larger base. The simulations predict the filling time, pressure distribution, volumetric shrinkage, stress distribution, etc., of the microcomponent.